Comparative exercising children with congenital clubfoot and peers - Mykhajlova N.E (Kharkov National Pedagogical University, 2012)
The data on the performance of jumping exercises and walking of children with congenital clubfoot and healthy peers were considered. Analysis of the results of the exercises revealed significant differences, and showed that children perform jumping exercises was heavier than the exercise of walking. In healthy children performing the exercises on walking caused no problems, they have fulfilled their own, but some with only minor errors. The study revealed a significant deterioration in exercise performance of children with congenital clubfoot compared with healthy peers.